دور الدافعية الذاتية واستراتيجيات تعلّم اللغات في إجادة اللغة العربية لدى طلبة جامعة العلوم الإسلامية الماليزية: دراسة مسحية تحليلية - Moza Othman Mubarak
A second language or foreign language proficiency substantially depends on social and psychological factors. There is also a consensus among second language experts that language learning success or failure is due to three main factors, which are teacher, student and curriculum. This new holistic understanding of language learning processes changed experts’ views on how second language teaching and learning should be conducted, as they noted that teaching of a teacher does not necessarily help students’ acquirement of knowledge. Although that second language studies in Western countries were empirical in nature, the study of Arabic Language as a second or foreign language is still largely theoretical. Furthermore, studies have shown that major challenges face second language learners such as lack of motivation and ineffective language strategies, which can lead to a loss of confidence and consequently to lack of language proficiency. Hence, this study attempts to investigate possible relation between intrinsic motivation and language learning strategies among students of the Islamic Science University of Malaysia. A total of 191 students from the university were randomly selected using simple sampling. Using Multiple Linear Regression, it was found that there is a strong statistical relationship between intrinsic motivation and the use of effective language strategies on one hand, and Arabic language proficiency on the other. Moreover, the study found that females were more motivated to learn Arabic language and use effective language strategies than their male counterparts, which consequently affect the level of their proficiency in Arabic language. The study recommended that the teachers should make Arabic language more interesting and attractive to the learners, and teach them how to employ effective strategies to acquire Arabic language.